Introduction to computer networks and cybersecurity - Wu, Chwan-Hwa; Irwin, J. David (Boca Raton : CRC Press, 2013)
'Draft Introduction to Computer Networking and Cybersecurity To the Student It is difficult to overstate the importance of computer networks and network security in today's world. They have become such an integral part of our existence that only a moment's reflection is required to delineate the many ways in which they impact essentially every aspect of our lives. For example, from a personal point of view one need only consider the impact that such things as wireless phones, texting, Facebook, Twitter, online billing and the like have had on the way we interact with one another and conduct various aspects of our lives. From a business perspective, it is clear that commerce is an ever growing global enterprise, dominated by digital transactions and conducted at unbelievable speeds via the Internet. In this environment, paper transactions are rapidly disappearing, and thus there is an expanding need for individuals who understand computer networks and their many facets and ramifications. This knowledge is becoming a prerequisite for living and working effectively in today's highly technical environment in which advances in computer networks and security technology change almost daily.'--
Includes bibliographical references and index.
Keywords: Computer networks; Computer networks -- Security measures